2004
DOI: 10.1016/j.ejcts.2003.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopic surgery for pulmonary nodules: rationale for preoperative computed tomography-guided hookwire localization

Abstract: Preoperative CT-guided hookwire localization for pulmonary nodules is an effective technique which allows VATS resection of PN <10 mm located >15 mm from the pleural surface. Even when PN are subpleural but <10 mm, hookwire localization makes VATS resection faster. Apical and diaphragmatic localization of PN are limitations to the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
163
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(177 citation statements)
references
References 15 publications
10
163
2
2
Order By: Relevance
“…One major problem with hookwires is the rate of dislodgement, as a component of the wire is external to the chest. This complication has been shown at rates ranging from 0-7.5% (22,23). Average length of stay was 3 days for VATS patients (22).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…One major problem with hookwires is the rate of dislodgement, as a component of the wire is external to the chest. This complication has been shown at rates ranging from 0-7.5% (22,23). Average length of stay was 3 days for VATS patients (22).…”
Section: Discussionmentioning
confidence: 97%
“…Their experience with 21 patients resulted in one failed placement with minimal complications and a mean length of stay of 1 to 6 days (21). The technique of using a breast localization wire has been used in a number of other studies, with rates of successful thoracoscopic resection ranging from 80-100% (22)(23)(24). Complication rates ranged from 7.5-51%, and included mostly asymptomatic pneumothoraces (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to surgery time, we did not make a comparison between localization with and without the CT-guided hookwire system prior to VATS. However, Ciriaco et al (14) reported that hookwire localization made VATS resection quicker, independent of whether it was conducted with preoperative localization or not. In this study, the average surgery time was 40±7 and 75±12 min (P<0.001), and the average time of CT hookwire positioning was 20±10 min.…”
Section: Discussionmentioning
confidence: 99%
“…Ciriaco et al (2) described its use in a series of 53 VATS procedures in 2004, and successful identification rates over 95% can be achieved with this method by several authors in series over 50 cases (3)(4)(5). The potential pitfalls of this technique were the potential side effects of pneumothorax and bleeding, but also migration of the wire, when the lung collapses during surgery.…”
Section: Available Methodsmentioning
confidence: 99%